Interaction of Sb(III) with iron sulfide under anoxic conditions: Similarities and differences compared to As(III) interactions. (March 2018) - Han, Young-Soo; Seong, Hye Jin; Chon, Chul-Min; Park, Jin Hee; Nam, In-Hyun; Yoo, Kyoungkeun; Ahn, Joo Sung
Abstract: This study examined the reaction mechanism of arsenite, As(III), and antimonite, Sb(III), with iron sulfide and compared their pH-dependent reaction behaviors under strictly anoxic environments. The comparison of Sb(III) with As(III), based on their chemical similarity, may provide useful insight into understanding the geochemical behavior of the less studied Sb(III). The pH-dependent batch sorption studies revealed that As(III) and Sb(III) displayed similar removal trends with pH in terms of the removal efficiency. However, the aqueous As(III) species transformed to thioarsenite species, while aqueous Sb(III) species remained inert under the highly sulfidic anoxic system. An X-ray absorption spectroscopy study demonstrated the reaction of As(III) and Sb(III) at acidic pH was closely related to the precipitation of sulfide minerals As2 S3 and Sb2 S3, respectively, as a consequence of the reaction with sulfide produced through mackinawite dissolution. Meanwhile, the removal at basic pH was inferred as a surface reaction, possibly through surface complexation, surface-precipitation, or both. In this study, the pH-dependent Sb(III) uptake mechanisms proved to be similar to the corresponding mechanisms for As(III) uptake, with mackinawite demonstrating a superior capacity to scavenge Sb(III) in ferrous and sulfide-rich reducing environments. Graphical abstract: Highlights: Interaction of Sb(III) with FeS was tested under acidic and basic pH conditions. The reaction mechanisms of Sb(III)FeS and As(III)FeS were compared. In both Sb(III)- and As(III)FeS systems, pH was revealed as an important controlling parameter. Under acidic conditions the dominant reaction process was precipitation of as sulfide minerals. Surface complexation was the dominant reaction process under basic pH conditions.